Evaluating the role of simulation in healthcare innovation: recommendations of the Simnovate Medical Technologies Domain Group. (24th March 2017) - Madani, Amin; Gallix, Benoit; Pugh, Carla M; Azagury, Dan; Bradley, Paul; Fowler, Dennis; Hannaford, Blake; Macdonald, Sumaira; Miyasaka, Kiyoyuki; Nuño, Natalia; Szold, Amir; Verter, Vedat; et al.
Abstract : Background: Innovation in healthcare is the practical application of new concepts, ideas, processes or technologies into clinical practice. Despite its necessity and potential to improve care in measurable ways, there are several issues related to patient safety, high costs, high failure rates and limited adoption by end-users. This mixed-method study aims to explore the role of simulation as a potential testbed for diminishing the risks, pitfalls and resources associated with development and implementation of medical innovations. Methods: Subject-matter experts consisting of physicians, engineers, scientists and industry leaders participated in four semistructured teleconferences each lasting up to 2 hours each. Verbal data were transcribed verbatim, coded and categorised according to themes using grounded theory, and subsequently synthesised into a conceptual framework. Panelists were then invited to complete an online survey, ranking the (1) current use and (2) potential effectiveness of simulation-based technologies and techniques for evaluating and facilitating the product life cycle pathway. This was performed for each theme of the previously generated conceptual framework using a Likert scale of 1 (no effectiveness) to 9 (highest possible effectiveness) and then segregated according to various forms of simulation. Results: Over 100 hours of data were collected and analysed. After 7 rounds of inductive data analysis, a conceptual framework of the product life cycle was developed. This framework helped to define and characterise the product development pathway. Agreement between reviewers for inclusion of items after the final round of analysis was 100%. A total of 7 themes were synthesised and categorised into 3 phases of the pathway: 'design and development', 'implementation and value creation' and 'product launch'. Strong discrepancies were identified between the current and potential roles of simulation in each phase. Simulation was felt to have the strongest potential role for early prototyping, testing for safety and product quality and testing for product effectiveness and ergonomics. Conclusions: Simulation has great potential to fulfil several unmet needs in healthcare innovation. This framework can be used to help guide innovators and channel resources appropriately. The ultimate goal is a structured, well-defined process that will result in a product development outcome that has the greatest potential to succeed.